PERLINDUNGAN HUKUM TERHADAP ANAK YANG DIPEKERJAKAN (UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK) - Putra Hamadah, Fasal Arif (JURNAL LEGISIA, 2021)
The complexity of the problems regarding children being employed is endless. The problem of adult workers is not over even though there is already a legal umbrella especially with regard to child labor which requires extra and more specific attention. Not only intersect with the legal side of child protection, but also intersect with the side of human rights (HAM) where the rights of the child even though he as a child worker must still be protected and protected. Based on an analysis of Indonesian laws and regulations governing protection for child labor, the following forms of protection for child labor are found: prohibiting the recruitment of child labor, but exceptions can be given for: aged between 13-15 years old for do light work as long as it does not interfere with the development and physical, mental and social health of the child, written permission from parents or guardians, work agreements between employers and parents or guardians, maximum working time of 3 (three) hours, is carried out during the day and does not interfere school time, occupational safety and health, clear employment relations, and receiving wages in accordance with applicable regulations. Keywords : Legal protection, Children, Regulations.